LiMnPO4 olivine as a cathode for lithium batteries - Bakenov, Zhumabay; Taniguchi, Izumi (Research Gate, 2011)
The olivine structured mixed lithium-transition metal phosphates LiMPO4 (M = Fe, Mn, Co) have attracted tremendous attention of many research teams worldwide as a promising cathode materials for lithium batteries. Among them, lithium manganese phosphate LiMnPO4 is the most promising considering its high theoretical capacity and operating voltage, low cost and environmental safety. Various techniques were applied to prepare this perspective cathode for lithium batteries. The solution based synthetic routes such as spray pyrolysis, precipitation, sol-gel, hydrothermal and polyol synthesis allow preparing nanostructured powders of LiMnPO4 with enhanced electrochemical properties, which is mostly attributed to the higher chemical homogeneity and narrow particle size distribution of the material. Up-to-date, the LiMnPO4/C composites prepared by the spray pyrolysis route have the best electrochemical performance among the reported in the literature.
Keywords: spray pyrolysis; LiMnPO4; lithium secondary batteries; cathode materials